Urban 110 kV indoor substation noise analysis and control schemes: A real case study. (1st December 2021) - Wang, Lv; Geng, Mingxin; Bai, Xiaochun; Ma, Jiangang; Zhao, Yalin; Shen, Chen; Yang, Bin
Highlights: Excessive noise emission problems of an urban 110kV indoor substation are discussed and tackled comprehensively in this paper. Dynamic vibration absorber with the target noise reduction frequency at 100Hz is firstly designed and applied in actual 110kV transformer, as a positive attempt to control the noise from the source. A M-typed dissipative muffler and a hybrid muffler are designed and implemented to control the additional noise radiation by the ventilation devices. After the integrated noise abatement project, the overall acoustic environment are improved and the noise level at the boundary of substation could meet the acoustic environmental quality standard of China. Abstract: As an important node in urban city, power substation provides the clean energy to thousands of households, ensuring a stable and high quality of urban life. However, the influence of noise emission from substation is always underestimated. With the improvement of environmental consciousness, making the substations quietly hidden in urban cities becomes an urgent issue which should be thoroughly considered. A real case is presented in this paper to vividly reflect how such a comprehensive noise issue is faced and tackled through proper techniques and novel applications. Based on the low-frequency noise characteristics of 110 kV power transformers and the limited space features of indoor substation, integrated noise control schemes are proposed with consideration of low-noise design of ventilation and heat dissipation systems. Dynamic vibration absorber is firstly investigated and designed to minimize the vibration of transformer tank. After the practical implementation, the acoustic environment is reevaluated and the measurement results verified the noise control effect. Consequently, the acoustic environment quality within and out of substation is improved and the negative impact of urban substation is controlled.